Autofill Browser Extension: A User-Friendly Solution to Optimize Metadata Workflow in Digital Repositories. Issue 1 (2nd January 2016) - Yang, Le; Zeng, Qingmin
Abstract : Facing a complex metadata environment, it is challenging to implement strategies for optimizing metadata workflows in digital repositories. Running scripted applications and batch processing cost libraries additional resources, while not reducing time implementing metadata. In order to improve the efficiency of metadata batch processing, the authors propose an open source browser extension that can easily be installed and executed for any digital repository. The authors also suggest that functional fixedness issues exist in the library profession and encourage librarians to discover solutions to address such issues and to improve library works.